Emotions in professional relations and employees’ health as exemplified by the teacher’s profession - Stadnyk, Magdalena; Szczygieł, Dorota; Książek, Janina (Polish Journal of Public Health, 2012)
Introduction. The teacher’s profession demands being in constant and intensive contact with other people, which entails a significant emotional strain and may, as a consequence, lead to health problems. Aim. The purpose of the study was to analyze the interrelations between the teachers’ health and the emotions they experience in contacts with students, and the ability to control the emotional states experienced. Material and methods. The study included 100 teachers, of whom 91 were women and 8 were men (one participant did not state the sex). Their health condition was examined by means of GHQ-12. The PANAS scale was used to evaluate positive and negative affectivity, and the INTE questionnaire to measure the emotional intelligence level. Declared emotions were measured using a questionnaire developed for the purposes of this paper. Results. The relationship between negative emotions and health was found during the control of seniority and dispositional variables: positive and negative affectivity and emotional intelligence. The level of health disorders in the examined teachers negatively correlates with emotional intelligence (r=-0.43, p<0.01) and positive affectivity (r=-0.43, p<0.01). And the level of health disorders correlates positively with negative affectivity (r=0.36, p<0.01) and experiencing negative emotions (r=0.42, p<0.01). However, experiencing positive emotions more frequently is not connected with a lower level of health-related problems (r=-0.15, p>0.05). Discussion. The strongest predictor of general health among the dispositional variables included in the study proved to be emotional intelligence. Nevertheless, the general health of the teachers studied is affected by a number of factors, both personality-related and dispositional as well as the situation or rather the negative emotions aroused by different events associated with contacts with students. Conclusions. Health is affected not only by the experiencing of negative emotions but also by competent work and the way of managing emotions. These skills play an important role not only in the teacher’s profession but also in other social professions.